EFFECTIVENESS OF USING MCH BOOKS AND MONSCA APPLICATIONS IN THE IMPLEMENTATION OF 14 T ANTENATAL SERVICE STANDARDS - Rahmawati Rahmawati; Syarif Syafruddin; Nontji Wena (Poltekkes Kemenkes Bandung, 2020)
The component of antenatal care received by pregnant women is classified as incomplete because the implementation of standard pregnancy services is still using conventional methods. There are obstacles faced by midwives, such as the limited time in a recording, which has an impact on the declining quality of antenatal care standards. This research aims to compare the effectiveness of the use of KIA books and MONSCA applications in midwives in the application of the standard Antenatal service 14 T. This research was conducted in Puskesmas Tanete and Puskesmas Bontobangun Bulukumba District. The method used in the study is experimental quasi (pre-test post-test nonequivalent control design). Using a sample of midwives in this study, as many as 36 people were divided into two groups (18 intervention groups and 18 control groups). The sampling technique in this study used purposive sampling. Data were analyzed using the Mann-Whitney Test. The results showed that there was a difference in the effectiveness of using KIA books with MONSCA applications, MOSCA's applications were easier to use, faster, safer, and more accurate than KIA books. It can be concluded that the MONSCA application is more effective than KIA books. Key words: Effectiveness, Android-based Smart Continuity of Care application, KIA book, Antenatal service 14 T